Leadership stability in relation to board-superintendent alignment: a selective analysis of board and superintendent co-governance pillars in Kansas - Krug, Chad A. (Kansas State University, 2020)
Leadership stability matters, especially at the district level, for frequent superintendent turnovers can have disruptive effects on staff morale, student performance, and organizational finance (e.g., Alsbury, 2008; Banicki & Pacha, 2011; Diem, Frankenberg, & Cleary, 2015; Grissom & Andersen, 2012; Grissom & Mitani, 2016). Optimally, the school board and superintendent would work orchestrally to provide quality and equitable education to all children as the core of district governance, while attending to other stakeholders’ needs within the district and local communities. Yet, research consistently points to the role confusion associated with the complexities of the superintendent-board arrangement for high turnover in superintendency, due to power structures and issues such as micromanaging involved in such relationships (e.g., Brunner, 1998; Cole & Holland, 2017; Mountford, 2004). This study reported here examined the notion of superintendent-board leadership alignment and its effects on the district leadership stability. Equally important if not more is that this study tested such an underlying structure of (mis)alignment, using a self-designed survey instrument. The population for this study was the public school superintendents of Kansas and their respective board presidents. Participants completed an online survey that contained demographic items and items on leadership preferences across five pillars of effectiveness. The four guiding research questions were: (a) How do superintendents perceive their leadership preferences? (b) How do school board presidents perceive the boards’ leadership preferences? (c) To what extent does the level of alignment of superintendent-board leadership preferences impact the tenure of the district superintendent?, and (d) What are the relationships between district size measured by student enrollment and the level of alignment of superintendent-board leadership preferences? Of the 282 possible superintendents, 202 completed the questionnaire; and out of the 286 possible board presidents, 158 completed the questionnaire. There were 133 pairs of superintendents and board presidents; in other words, the pair served in the same school district. The validity and reliability of the survey were measured, using exploratory factor analysis and Cronbach’s alphas. Logistic regressions and simple correlation analyses were conducted to examine relationships between alignment and superintendent tenure as well as district size and alignment. The exploratory factor analysis results revealed that there were five factors, that is, five possible underlying tenets for board-superintendent leadership alignment. They were named as “Two-way communication,” “Alignment through mission and vision,” “Collegiality and collaboration,” “Student achievement and quality instruction,” and “Procedural.” Only Factor 2, “Alignment through mission and vision” was found to be significantly related to superintendent tenure. In terms of district size’s effects on leadership alignment, only Factor 3, “Centering on collegiality and collaboration” was found to be have a significant relationship with district size. From this study’s findings, recommendations are offered to improve superintendent and board member governance structures as well as the focus on aspects of the shared governance role necessary to increase district stability.
Keywords: Alignment; Board of education; Governance teams; Superintendent; Leadership preferences; Pillars of stability